LED-pumped room-temperature solid-state maser - Sophia Long; Lisa Lopez; Bethan Ford; François Balembois; Riccardo Montis; Wern Ng; Daan M. Arroo; Neil McN. Alford; Hamdi Torun; Juna Sathian (Communications Engineering)
Abstract Room-temperature MASERs (Microwave Amplification by Stimulated Emission of Radiation) amplify electromagnetic waves at microwave frequencies with minimal noise. We demonstrate a cost-effective LED-pumped maser using pentacene-doped para-terphenyl as the gain medium. Here, we show that LED light, which is brightness-enhanced and guided via a cerium-doped yttrium aluminium garnet luminescent concentrator, achieves persistent maser emission at 1.45 GHz with a duration of 200 µs and a microwave output power of 0.014 mW, surpassing previous non-laser pumped systems. Operating at low voltage, the LED-pumped maser ensures safety, reduced costs, and simple integration. Potential applications include sensitive magnetic resonance imaging, portable atomic clocks, quantum technologies, and enhanced deep-space radio astronomy.